Teaching of the issue of first aid at schools in the Czech Republic - Kavan, Štěpán (Wyższa Szkoła Bezpieczeństwa Publicznego i Indywidualnego "Apeiron", 2018)
The paper focuses on examining the implementation of first aid in schools. It reflects the obligation of schools to provide first aid in the event of health problems or risks to the life of students and school staff. The second area deals with first aid education of students so that they can gain the competencies to provide first-aid in practical life. The basic possibilities of education of first aid in general basic education programmes are characterized. The characteristics of first aid development in schools are developer in order to gain a comprehensive understanding of the first aid education issue. A historical-comparative analysis is used as the method of research.
Výuka problematiky první pomoci na školách v České republice
Keywords: first aid; general education programme; human protection under current risks and emergencies; první pomoc; rámcové vzdělávací programy; ochrana člověka za běžných rizik a mimořádných událostí